2014
DOI: 10.1155/2014/672714
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Diagnostic Expert Systems in Rheumatology: Where Do We Stand in 2014?

Abstract: Background. The early detection of rheumatic diseases and the treatment to target have become of utmost importance to control the disease and improve its prognosis. However, establishing a diagnosis in early stages is challenging as many diseases initially present with similar symptoms and signs. Expert systems are computer programs designed to support the human decision making and have been developed in almost every field of medicine. Methods. This review focuses on the developments in the field of rheumatolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 54 publications
0
13
0
1
Order By: Relevance
“…A direct test of this hypothesis will require considering how best to provide physicians with EWS results or incorporate the additional cues used by physicians into EWSs. Such integration is an area for ongoing and future research, noting that prior efforts to integrate artificial intelligence systems into medical decision making have largely failed to achieve widespread adoption 25–27…”
Section: Discussionmentioning
confidence: 99%
“…A direct test of this hypothesis will require considering how best to provide physicians with EWS results or incorporate the additional cues used by physicians into EWSs. Such integration is an area for ongoing and future research, noting that prior efforts to integrate artificial intelligence systems into medical decision making have largely failed to achieve widespread adoption 25–27…”
Section: Discussionmentioning
confidence: 99%
“…Despite the elapsed time, such systems are still not part of standard rheumatology care. Alder et al concluded in a review in 2014 that the validation process of rheumatology DDSS was in general underappreciated and none of the systems seemed to have succeeded in daily practice (12).…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…Digital diagnostic decision support systems (DDSS) and in particular online self-referral (OSR) systems and symptom checkers (SC) promise to accelerate diagnosis in rheumatic diseases (11)(12)(13) and improve health care e ciency. Currently more than 100 SCs exist (14) and are increasingly used by patients.…”
Section: Introductionmentioning
confidence: 99%
“…A useful fuzzy expert system was developed by Azim and colleagues [8] for the detection of fatigue among drivers in order to prevent road accidents. Alder and colleagues [9] conducted a review on different expert systems that have been developed and applied Rheumatology. Duan and colleagues [10] applied the knowledge of prefix-tree to create a Nursing care recommender system.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%